A Predictive Model for Steady State Ozone Concentration at an Urban-Coastal Site - Alghamdi, Mansour A.; Al-Hunaiti, Afnan; Arar, Sharif; Khoder, Mamdouh; Abdelmaksoud, Ahmad S.; Al-Jeelani, Hisham; Lihavainen, Heikki; Hyvärinen, Antti; Shabbaj, Ibrahim I.; Almehmadi, Fahd M.; Zaidan, Martha A.; Hussein, Tareq; et al. (International journal of environmental research and public health, 2019)
Ground level ozone (O3) plays an important role in controlling the oxidation budget in the boundary layer and thus affects the environment and causes severe health disorders. Ozone gas, being one of the well-known greenhouse gases, although present in small quantities, contributes to global warming. In this study, we present a predictive model for the steady-state ozone concentrations during daytime (13:00–17:00) and nighttime (01:00–05:00) at an urban coastal site. The model is based on a modified approach of the null cycle of O3 and NOx and was evaluated against a one-year data-base of O3 and nitrogen oxides (NO and NO2) measured at an urban coastal site in Jeddah, on the west coast of Saudi Arabia. The model for daytime concentrations was found to be linearly dependent on the concentration ratio of NO2 to NO whereas that for the nighttime period was suggested to be inversely proportional to NO2 concentrations. Knowing that reactions involved in tropospheric O3 formation are very complex, this proposed model provides reasonable predictions for the daytime and nighttime concentrations. Since the current description of the model is solely based on the null cycle of O3 and NOx, other precursors could be considered in future development of this model. This study will serve as basis for future studies that might introduce informing strategies to control ground level O3 concentrations, as well as its precursors’ emissions.